The Moderating Effect of Procedural Justice on the Effectiveness of the Balanced Scorecard in Improving Managerial Performance through Organizational Commitment - Supriyadi, Supriyadi (Gadjah Mada International Journal of Business, 2010)
This study extends prior studies on the effectiveness of theBalanced Scorecard (BSC) to improve managerial performancedone by Lau and Mosser (2008) and Lau and Sholihin (2005).Specifically, the study empirically tests the moderating effects ofprocedural justice on the relationship between the financial andnonfinancial dimensions of BSC and managerial performance. Italso tests the impact of organizational commitment on performance.Based on survey data from 76 respondents, the results indicate thatperceived procedural justice in the use financial and nonfinancialdimensions of the BSC is associated with managersâ organizationalcommitment. It further finds that organizational commitment ispositively related to performance. The study extends the literatureby providing empirical evidence about the moderating effect ofprocedural justice on the relationship between the financial andnonfinancial dimensions of BSC and organizational commitment.Keywords: balanced scorecard; organizational commitment; financial measures;managerial performance; moderating effect; nonfinancial measures;procedural justice